Drug delivery to solid tumors: the predictive value of the multicellular tumor spheroid model for nanomedicine screening - Millard M (Dove Medical Press, 2017)
Marie Millard,1,2 Ilya Yakavets,1–3 Vladimir Zorin,3,4 Aigul Kulmukhamedova,1,2,5 Sophie Marchal,1,2 Lina Bezdetnaya1,2 1Centre de Recherche en Automatique de Nancy, Centre National de la Recherche Scientifique UMR 7039, Université de Lorraine, 2Research Department, Institut de Cancérologie de Lorraine, Vandœuvre-lès-Nancy, France; 3Laboratory of Biophysics and Biotechnology, 4International Sakharov Environmental Institute, Belarusian State University, Minsk, Belarus; 5Department of Radiology, Medical Company Sunkar, Almaty, Kazakhstan Abstract: The increasing number of publications on the subject shows that nanomedicine is an attractive field for investigations aiming to considerably improve anticancer chemotherapy. Based on selective tumor targeting while sparing healthy tissue, carrier-mediated drug delivery has been expected to provide significant benefits to patients. However, despite reduced systemic toxicity, most nanodrugs approved for clinical use have been less effective than previously anticipated. The gap between experimental results and clinical outcomes demonstrates the necessity to perform comprehensive drug screening by using powerful preclinical models. In this context, in vitro three-dimensional models can provide key information on drug behavior inside the tumor tissue. The multicellular tumor spheroid (MCTS) model closely mimics a small avascular tumor with the presence of proliferative cells surrounding quiescent cells and a necrotic core. Oxygen, pH and nutrient gradients are similar to those of solid tumor. Furthermore, extracellular matrix (ECM) components and stromal cells can be embedded in the most sophisticated spheroid design. All these elements together with the physicochemical properties of nanoparticles (NPs) play a key role in drug transport, and therefore, the MCTS model is appropriate to assess the ability of NP to penetrate the tumor tissue. This review presents recent developments in MCTS models for a better comprehension of the interactions between NPs and tumor components that affect tumor drug delivery. MCTS is particularly suitable for the high-throughput screening of new nanodrugs. Keywords: nanodrug, tridimensional model, distribution, accumulation, cytotoxicity